Art in Question. - Raney, Karen (International Journal of Art & Design Education, 2003)
Abstract Art in Question is one of the outcomes of the Arts Council's research into visual literacy. The book was launched on 11th March, 2003 at Bloomberg, London, with a conversation between the author and two of the contributors to the book, writer Sadie Plant and Professor of English and Art History, WJT Mitchell. This article is an edited transcript of that conversation. Plant and Mitchell begin by talking about points of uncertainty in their work which moved it forward. They go on to discuss the so-called ‘pictorial turn’, and ways in which contemporary art and film have taken on the subjects of bioengineering and the electronic revolution. Referring to images from Poussin and Dada, to a WWI recruiting poster and, Jurassic Park, the conversation suggests that both technological and political developments are posing fresh challenges to the visual arts.